Academic Staff Awareness of Institutional Repositories (IRs) in Tanzania Universities - Kayungi, Paulina Nyangoma; Ndenje-Sichalwe, Esther; Manda, Paul A. (University of Dar es Salaam Library Journal, 2021)
This paper presents the results of an investigation on the awareness of Institutional Repositories (IRs) among academic staff in Tanzania ' s universities. The study employed descriptive research design and mixed methods approaches. The study was conducted in four institutions: The University of Dar es Salaam (UDSM), Muhimbili University of Health and Allied Sciences(MUHAS), Sokoine University of Agriculture(SUA) and Saint Augustine University of Tanzania(SAUT). It employed both qualitative and quantitative techniques to collect, process and analyse data. The study found that most of respondents were not conversant with strategies used to collect scholarly works for their universities IRs. Besides, they were not aware of self-archiving practices of their scholarly works in their respective university IRs. The findings further indicate that, institutional websites and academic colleagues are the main sources of information on IRs. The study recommends implementation of diverse marketing strategies and conducting regular training, workshops and seminars to improve awareness, skills and knowledge about IRs among academic staff.